The Synthesis of Three Chelating Reagents Derived from Chloric Acid - Boag, David (My University, 1987)
Three cholic acid derived chelating reagents were synthesized. They were synthesized by the attachment of existing chelating ligands onto the side chain of cholic acid via a spacer chain which connects cholic acid and chelate. The incorporation of the ligands EDTA, DTPA and DHPTA onto suitable cholic acid derivatives was performed to produce the respective cholic acid derivatives: cholic acid -EDTA, cholic acid-DTPA, and cholic acid-DHPTA. The synthesis of a fourth chelating reagent was attempted by attaching HEDTA onto the cholic acid side chain but was unsuccessful . A complete account of the three syntheses and one partial synthesis are outlined in this thesis.
Keywords: Chelating Reagents; Cholic Acid; chelating ligands; acid